2015
DOI: 10.1097/mib.0000000000000561
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vedolizumab as Induction Therapy in Refractory IBD Patients

Abstract: Background Vedolizumab (VDZ) demonstrated efficacy in Crohn's disease (CD) and ulcerative colitis (UC) in the GEMINI trials. Our aim was to evaluate the efficacy of VDZ at week 14 in inflammatory bowel disease (IBD) in a multicenter cohort of patients. Methods Patients at Massachusetts General Hospital and Brigham and Women's Hospital were considered for inclusion. VDZ (300mg) was administered at weeks 0, 2, 6 and 14. Efficacy was assessed using the Harvey Bradshaw index (HBI) for CD, the simple clinical col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
144
6
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(171 citation statements)
references
References 28 publications
17
144
6
4
Order By: Relevance
“…An adverse event was seen in 10.5% of patients, five of whom were worsening arthropathy and one a new pyoderma gangrenosum (see [22]. VDZ led to a clinical improvement in the majority of IBD patients and was well tolerated, however, the adverse events were higher than expected [15,22].…”
Section: Vedolizumabmentioning
confidence: 95%
See 2 more Smart Citations
“…An adverse event was seen in 10.5% of patients, five of whom were worsening arthropathy and one a new pyoderma gangrenosum (see [22]. VDZ led to a clinical improvement in the majority of IBD patients and was well tolerated, however, the adverse events were higher than expected [15,22].…”
Section: Vedolizumabmentioning
confidence: 95%
“…The integrins α4β1, α4β7, αEβ7 and αLβ2 are the main receivers who contribute to this infiltration [12]. The α4β7 integrin, expressed in auxiliary and memory T cells, bind in mucosal vascular addressin cell adhesion molecular 1 (MAdCAM-1) expressed on the endothelial cells, playing an important role in the coupling of the T cells to the membrane [15]. Anti-integrin therapy modulates the inflammation by binding some of these integrins, which has an overall effect of preventing inflammation in the gut through inhibition of leukocyte migration into the mucosa.…”
Section: Anti-integrin Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, vedolizumab may be useful for patients who are not responsive to anti-TNF treatment. Other cohort studies also indicated a relatively high clinical response (50-53 % at week 14) [52,53] or marked decreases in the partial Mayo score at week 6 [54], which was observed although the patients had not been randomized. The adverse effects were comparable between the vedolizumab group and placebo group in most studies.…”
Section: Vedolizumabmentioning
confidence: 95%
“…Nevertheless, similar to anti-TNFα agents, a significant proportion of patients (≈ 40%) failed to reach or to maintain remission in response to vedolizumab. In real-word cohorts, the primary response rate to vedolizumab is effectively similar in UC and CD patients, 40-60% of patients [5,6]. Lack of response or need for dose optimization occurs in 40-60% of IBD patients during the maintenance phase [7,8].…”
mentioning
confidence: 99%